Enhancing Cell Penetration Efficiency of Cyclic Oligoarginines Using Rigid Scaffolds - Csaba Bató; Ildikó Szabó; Zoltán Bánóczi (MDPI AG, 2023)
Delivering therapeutic agents into cells has always been a major challenge. In recent years, cyclization emerged as a tool for designing CPPs to increase their internalization and stability. Cyclic ring(s) can protect the peptide from enzymatic degradation, so cyclic peptides remain intact. Therefore they can be good carrier molecules. In this work, the preparation and investigation of efficient cyclic CPPs are described. Different oligoarginines were designed to conjugate with rigid aromatic scaffolds or form disulfide bonds. The reaction between the scaffolds and the peptides forms stable thioether bonds, constraining the peptide into a cyclic structure. The constructs presented very efficient internalization on cancerous cell lines. Our peptides use more than one endocytic pathway for cellular uptake. In this way, short peptides, which can compete with the penetration of well-known CPPs such as octaarginine (Arg8), may be synthesized through cyclization.